Hubungan peranan teman sebaya dengan perkembangan sosial emosional siswa-siswi kelas X di SMK Negeri 2 Sewon Bantul Yogyakarta - Evi Suryandari; Sulistiyawati Sulistiyawati; Lia Endriyani (Caring : Jurnal Keperawatan, 2019)
Teenagers are the time to mature with the rapid development of physical, cognitive, emotional and social. Not all adolescents get through smoothly. Emotional, social problems marked aggressiveness and delinquency during 2016 in DIY recorded 43 cases of student brawl, perpetrators of children aged 14-18 years. One of the factors that influence is peers. Teens spend a lot of time hanging out with their peers, so peers are influential in emotional-social development. To know the relationship of peer role with emotional-social development of students at SMK Negeri 2 Sewon Bantul Yogyakarta. The design of this research is analytic descriptive with a cross-sectional approach — the sampling condition used cluster random sampling method with 107 student sample. The research instrument used is a peer role questionnaire and emotional, social development questionnaire — bivariate statistical test using Pearson. The majority of respondents were women of 81 people (75.7%), 16 years of age 77 people (72%), peer role was 81 people (75.7%), and emotional, social development both 101 people (94.4 %). The role of peers is with emotional-social development, both 76 (71.0%). Result of bivariate test analysis obtained p-value = 0,028 and correlation coefficient value 0,213. There is a significant relationship between the role of peers with emotional-social development in the students at SMK Negeri 2 Sewon Bantul Yogyakarta